Mercury Accumulation in Liver, Kidney, Pectoral Muscle and Breast Feathers of Zarivar Wetland Common Coot (Fulicaatra) - Mansouri, Borhan; Majnoni, Farshid; Karimi, Hazhir Karimi (Science Journal of University of Zakho, 2013)
In this survey, the mercury concentration of kidney, liver, breast feathers and pectoral muscle was assayed in water bird, the Coot Fulicaatra. Bird samples were collected from November 2011 to January 2012 throughout the Zarivar wetland in western of Iran, and mercury was assayed by using a Varian 220 atomic absorption spectrophotometer; the results were given as µg/g. Results showed that the mercury concentration in the Coot were decreased in sequence of liver >feather > kidney> pectoral muscle. Also, the results indicated that the levels of the mercury concentration in the Coot were higher in females than in males. Mercury concentrations were different between the tissues of Coot, but there was no difference between sex (male vs. female; except mercury in muscle).